Geotourism Concept Development in the Basis of Environment Sustainability, Socioculture, and Natural Science Wealth: A Case Study in Indonesia - MARLINA, Endy; HERAWAN, Tutut (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.11.1(41).17, 2020)
This paper presents geotourism development as a development framework of Gunungkidul Regency, Indonesia. This concept has been formulated in the consideration of policy direction of local and national tourism development, requirement of Geopark Global Network concept, consideration of environment, social and cultural environment and the demand of trend of the tourism interest improvement among society. This research was conducted with the urgency of: (1) the importance of geodiversity and geoheritage preservation as the unrenewable resources; (2) the important values of geodiversity and geoheritage that have a valuable knowledge for the people and their environment; (3) the importance of biodiversity as the environment wealth that plays an absolute role towards the balance of the environment; (4) The significant role of the wealth of socio-culture of people (cultural diversities) as a local wisdom that has a great power in the development process and (5) the urgency of the improvement of independency of tourism entrepreneurship as the accurate strategy in the development program for people prosperity. The direction of the geotourism development has been formulated through the synthesis of various analyses covering the analysis on government policy, analysis on the potential of tourism attraction, and SWOT analysis. The dialogue of any analyses is required to guarantee the production of formulation in the accurate and synergic direction of geotourism with any various existing development directions. The direction of the empowerment of the living environment and natural resources shows the awareness of how very fundamental the balance, harmony and aptitude of ecology, society, economic and culture is.